O uso da terra e a distribuição dos casos de raiva bovina em Goiás, Brasil, 1985 - 2016 - Diogo Filho, Aníbal Anatólio; Santos, Adriana da Silva; Silva, Marcos Xavier; Oliveira, Tiago Mendonça de; Coelho, Adilson Márcio; Patez, Daniel Climaco (Multi-Science Journal, 2017)
não há